PERFORMANCE ENGINE 1108 CC MENGGUNAKAN BAHAN BAKAR RON 88 DAN RON 92 - Nofriyandi.R Nofriyandi.R; Rina Rina; Haznam Putra (Ensiklopedia of Journal, 2019)
This experimental study aims to compare the performance and Spesific Fuel Consumsion (Sfc) where were produced from RON 88 fuel and RON 92 fuel with T101D Automotive engine test bed, with optionals tool. Engine gasoline type 1.1 8V was used in this study. The difference of torque which is caused by the use of RON 88 and RON 92 fuel is obtained. The highest torque at occurred 2500 rpm where the comparison between these two is about 4.458 %. Then, the performance of RON 88 has slight difference. The Spesific Fuel Consumption (sfc) of RON 92 fuel is lower than RON 88 fuel sfc. The lowest decrease (sfc) is 21.212% at 3700 rpm and the overall engine decline is 7.796%.